Effect of chronic exposure to prometryne on oxidative stress and antioxidant response in common carp (Cyprinus carpio L.) - Stara, Alzbeta; Kristan, Jiri; Zuskova, Eliska; Velisek, Josef (Pesticide biochemistry and physiology, 2013)
The effects of the triazine herbicide prometryne, commonly present in surface and ground waters, on oxidative stress and antioxidant status of common carp (Cyprinus carpio) were investigated. Fish were exposed to sublethal concentrations of prometryne (0.51, 8, and 80μg/l) for 14, 30, and 60 days. Activity of superoxide dismutase (SOD), catalase (CAT), and glutathione reductase (GR), as well as levels of thiobarbituric acid reactive substances (TBARSs) were assessed in brain, gill, intestine, liver, and muscle. After 14 days exposure, decreased GR activity in brain was observed for all prometryne-exposed groups compared with the controls. Changes were observed in SOD activity in brain and gill after 30 days in all exposure groups. Changes in CAT activity were observed only at the highest concentration (80μg/l) in liver and intestine after 60 days. The observed effects on carp antioxidant systems may be a defense against oxidative damage. The study demonstrated changes in antioxidant parameters and the importance of evaluating the potential long-term risk to fish of prometryne, at environmentally realistic concentrations (0.51μg/l). The results suggest that antioxidant responses may have potential as biomarkers for monitoring residual triazine herbicides in aquatic environments.
Keywords: střeva; Muscles; glutathionreduktasa; chemické látky znečišťující vodu; Oxidative Stress; Animals; Intestines; superoxiddismutasa; herbicidy; Carps; Prometryne; prometryn; antioxidancia; Fish Proteins; oxidační stres; Antioxidants; Glutathione Reductase; zvířata; Herbicides; Environmental Monitoring; monitorování životního prostředí; svaly; kapři; rybí proteiny; Superoxide Dismutase; Water Pollutants, Chemical